Determinants of Behavioral Style in Critical Situations: An Empirical Study of Empathy and Personality Dimensions - Kakhi Kopaliani; Nino Kiknavelidze (Modern Scientific Technology, 2025)
Behavioral styles play a critical role in regulating individual responses during interpersonal and conflict situations, particularly under conditions of heightened psychological pressure. Understanding the psychological determinants of these styles is essential for advancing both theory and applied interventions. The present study aimed to examine the determinants of behavioral styles in critical situations, with a specific focus on empathy dimensions and personality traits. A quantitative, cross-sectional survey was conducted on a Georgian population sample using three standardized instruments: the Thomas Conflict Mode Instrument to assess behavioral styles (rivalry, cooperation, compromise, avoidance, accommodation), the Interpersonal Reactivity Index (Davis) to measure empathy (fantasy, empathic concern, decentering, empathic distress), and the Big Five personality framework (extraversion, agreeableness, conscientiousness, neuroticism, openness to experience). Statistical analyses included descriptive statistics and correlation analyses to explore relationships among the studied variables. The results revealed significant associations between specific empathy dimensions, personality traits, and preferred behavioral styles in critical situations, suggesting that both affective-cognitive processes and stable personality characteristics contribute to behavioral regulation. These findings provide empirical support for an integrative model of behavioral style determinants. The study offers theoretical implications for understanding conflict behavior and practical implications for psychological assessment, conflict management, and intervention programs within sociocultural contexts.